Update in the treatment of cutaneous leishmaniasis - Sahar H Al-Natour (Wolters Kluwer Medknow Publications, 2009)
Background:Cutaneous leishmaniasis (CL) is still a major health problem in many countries including Saudi Arabia. Patients with CL are seen, not only by dermatologists, but also by pediatricians and community physicians. Knowledge of available treatment options is essential. Design: A literature review utilizing PubMed and Cochrane evidence-based library was undertaken in the last five years. Results : Several medications and therapeutic modalities are currently in use, though the gold standard remains systemic antimonials. Drug resistance and serious side effects preclude the use of available medications. Newer therapies like liposomal amphotericin B, miltefosine and pentamidine are being used; while it is hoped that other drugs like imiquimod, tamoxifen, PDT and pentamidine structural analogs being tested would offer better efficacy, easier administration and lower toxicity. Conclusion : After decades of little advance in the treatment of leishmaniasis, there are now several options with newer compounds and combinations of these.